Vascularized polypeptide hydrogel modulates macrophage polarization for wound healing. (1st January 2023) - Chen, Zhijie; Wang, Lianlian; Guo, Changjun; Qiu, Minglong; Cheng, Liang; Chen, Kaizhe; Qi, Jin; Deng, Lianfu; He, Chuan; Li, Xinming; Yan, Yufei
Abstract: Wound repair involves a sophisticated process that includes angiogenesis, immunoregulation and collagen deposition. However, weak revascularization performance and the lack of biochemical cues to trigger immunomodulatory function currently limit biomaterial applications for skin regeneration and tissue engineering. Herein, we fabricate a new bioactive polypeptide hydrogel (QK-SF) constituted by silk fibroin (SF) and a vascular endothelial growth factor mimetic peptide KLTWQELYQLKYKGI (QK) for tissue regeneration by simultaneously promoting vascularization and macrophage polarization. Our results showed that this QK-SF hydrogel can be prepared via an easy manufacturing process, and exhibited good gel stability and low cytotoxicity to cultured human umbilical vein endothelial cells (HUVECs) via both live/dead and cell counting kit-8 assays. Importantly, this QK-SF hydrogel triggered macrophage polarization from M1 into M2, as exemplified by the enhanced expression of the M2 marker and decreased expression of the M1 marker in RAW264.7 cells. Furthermore, the QK-SF hydrogel showed high capacity for inducing endothelial growth, migration and angiogenesis, which were proved by increased expression of angiogenesis-related genes in HUVECs. Consistent with in vitro findings, in vivo data show that the QK-SF hydrogel promoted M2 polarization, keratinocyte differentiation, and collagen deposition in the mouse skin wound model in immunohistochemistry assay. Furthermore, this QK-SF hydrogel can reduce inflammation, induce angiogenesis and promote wound healing as exemplified by the increased vessel formation and decreased wound area in the mouse skin wound model. Altogether, these results indicate that the bioactive QK-SF hydrogel plays dual functional roles in promoting angiogenesis and immunoregulation for tissue regeneration. Statement of significance: The QK-SF hydrogel plays dual functional roles in promoting angiogenesis and immunoregulation for tissue repair and wound healing. The QK-SF hydrogel can be prepared via an easy manufacturing process, and exhibited good gel stability and low cytotoxicity to cultured HUVECs. The QK-SF hydrogel triggered macrophage polarization from M1 into M2. The QK-SF hydrogel showed high capacity for inducing endothelial growth, migration and angiogenesis. The QK-SF hydrogel promoted M2 polarization, keratinocyte differentiation, and collagen deposition. Graphical abstract: Image, graphical abstract